A new algorithm for power distribution system planning - Ranjan, R. (Elsevier Science, 2002)
In this paper, an attempt has been made to develop a new algorithm for distribution system planning. The proposed algorithm does not require prior knowledge of candidate substation location and can automatically select location of a substation, the optimal feeder configuration and the optimal sizes of branch conductors while satisfying constraints such as current capacity, voltage drop and heuristic rules. Several algorithms are proposed for distribution systems planning. A generalized algorithm is developed for obtaining the optimal feeder path and the optimal location of substation on minimum loss criterion. Heuristic rules are incorporated in the above algorithm. Another algorithm is for branch conductor optimizations. Modified load flow method is also presented in the paper, which can handle composite load models. The load flow algorithm is used for solving radial distribution networks (RDN) and branch conductor optimization algorithm. The load flow algorithm and branch conductor optimization techniques are used as subroutine in the generalized distribution systems planning algorithm. Through numerical example the validity of proposed method is verified. (C) 2002 Elsevier Science B.V. All rights reserved.